Game-Based Assessment Research Trends in Education: Bibliometric Analysis in The Context of Islamic Religious Education - Fatimah, Fatimah; Hafidz, Hafidz (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to explore the development of Game-Based Assessment research, as well as identify opportunities for the development of Islamic Religious Education learning evaluation. Methodology: This study uses a bibliometric approach. Data sourced from Scopus obtained on January 23, 2026 with a focus on the publication of 2011-2026. This research has 3 stages, literature review, data search and cleaning process, and the last is data analysis. The data was analyzed using VosViewers, Ms.Excel, and Biblioshiny software. In the search for data, several inclusive criteria were set so that 101 articles were obtained for analysis. Results: The results of the study show that publications related to game-based assessments have increased significantly. The highest publication occurred in 2025, with 19 publications. The most publications are published by the United States as a developed country that discusses a lot of studies on game-based assessment. Thematic mapping reveals findings such as 21st century skills, evaluation methodologies, and feedback, reflecting new directions and potential innovations in advanced research. Overall, the bibliometric analysis shows that the game-based assessment research cluster is more developed in the context of general education and technology based learning, the keywords and themes that explicitly represent Islamic Religious Education do not emerge as the dominant cluster, indicating that the study of game-based assessment in the context of Islamic Religious Education assessment is still relatively limited in the literature. Applications/Originality/Value: This research contributes in the form of trend mapping of Game-based assessment directed at the need for learning evaluation of Islamic Religious Education in the digital era, as well as opening up opportunities for further research related to the development and application of game-based assessment in the evaluation of Islamic Religious Education learning.